Blater Charisma in Building Religiosity: An Effort to Maintain Family Image in Sampang District Madura - Shidqi Ahyani (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2024)
Abstract: In the life of Madurese society, Blater is a social group that becomes a community leader with courage, physical immunity, and a high kharim so that the community respects it. This research is field research with a qualitative approach. Data collection methods are carried out through interviews, observation, and documentation. The data obtained was analyzed to find research conclusions. The results showed that, first, in the formation of the Blater family, two ways are known, namely the charisma of the Blater in building religiosity in Disanah Village, Sampang Madura Regency, by earning a living for the wife's children and choosing a mate. Second, efforts to maintain the family image of the Blater community in Disanah Village, Sampang Madura Regency, are made using two methods, namely physical and non-physical protection.